The Culturally Responsive Teaching Approach (CRT) In Learning Observation Report Texts Based on Local Culture at SMP Negeri 8 Palembang - Rahmawati, Siti; Ramadhani, Risky; Al Faris, Mizan; Wilujeng, Insih (Riviera Publishing, 2025)
Education plays an important role in preserving the richness of local culture, including the culture of Palembang City which is rich in arts, Limas houses, culinary, and traditions. In the era of the independent curriculum, learning needs to be linked to the local context to be more meaningful and able to foster a love for one's own culture. The purpose of this community service is to improve students' understanding and skills in compiling observation report texts through the application of the Palembang culture-based Culturally Responsive Teaching (CRT) approach at SMP Negeri 8 Palembang. The solution is carried out through community service activities in the form of training and mentoring teachers in designing and implementing observation report text learning that integrates local cultural elements. The methods used include socialization of the CRT approach, assistance in preparing lesson plans and open modules, and direct assistance in implementing learning in the classroom. The activities are carried out collaboratively with teachers and students of grade VIII, with a focus on observing Palembang cultural objects and compiling culture-based observation reports. The outputs obtained are teaching modules for observation report texts based on Palembang culture, improved teacher skills in designing contextual learning, and increased motivation, participation, and students' abilities in compiling observation report texts. This community service also succeeded in fostering students' appreciation of local culture through relevant and enjoyable learning.